PENGARUH PEMBERIAN BERBAGAI DOSIS PUPUK KANDANG AYAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH (Allium ascalonicum L.) VARIETAS LEMBAH PALU - Budianto,Nirwan Sahiri, Ichwan S.Madauna, Agus (AGROTEKBIS, 2015)
This study aims to determine the effect of various doses of chicken manure on the growth and yield of onion (Allium ascalonicum L.). The research was conducted in the village of Sidera (Bolu Pountu Jaya), District of Sigi Biromaru, Sigi. In August 2014 up to October, 2014. This study used a Randomized Block Design (RBD) pattern is one factor that is with various doses of chicken manure consists of six levels. Thus, there are six treatments and each treatment was replicated three times as a group, so there are 18 experimental units. Data were analyzed using analysis of variance (ANOVA). Provision of chicken manure significantly affect the growth and yield of onion. Except at high observation plants after planting 8 weeks after planting chicken manure application had no significant effect. Provision of chicken manure at a dose of 10 tonnes per hectare yield plant height, number of leaves, number of tubers and tuber production better than the dose of other chicken manure.